ENVIRONMENTAL SAFETY AND EFFICIENT RESOURCE USE IN CONDENSED MILK PRODUCTION - Mohinur Sayitniyozovna Ismattova (American Journals Publishing, 2025)
This article examines the importance of environmental safety and efficient resource utilization in condensed milk production. It highlights the challenges faced by the dairy industry regarding energy consumption, water use, waste management, and sustainability. The essay discusses strategies for improving production efficiency while minimizing environmental impact, including the adoption of modern technologies, renewable energy, and sustainable supply chain practices. The role of policy, industry standards, and corporate responsibility in promoting eco-friendly dairy production is also analyzed.
Keywords: Condensed milk, environmental safety, resource efficiency, sustainability, dairy industry, energy conservation, waste management.